Forest Project’s Conceptualization: An experience conceived in layers: from theoretical thought to its visual representation - Furió-Vita, Dolores; Aragó Miñana, María del Mar (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The research that comprises El Bosque project combines a part of an artistic production through the development of an immersive experience with Virtual Reality technology, and a theoretical part that allows us to generate a journey through the different scenes, uniting them conceptually through the analysis of theories of conceptual referents extracting specific concepts that adjoin within ecological thought. Through this research we have made a selection, analysis and synthesis of different concepts and currents of thought of authors around ecology. Thus structuring the project of El Bosque and summarizing the foundations of a current and situated thought, which not only encompasses something related with ecology, but also participates and crosses everything that has to do with our life in the present.